• Упростите выражения:

    а) 4(4x-2)+7(1-6x)

    б) 0,3(x-5y-2)-0,8(2y-3x)

Ответы 2

  • а) 4(4x-2)+7(1-6x)=16х-8+7-42х=-26х-1б) 0,3(x-5y-2)-0,8(2y-3x)=0.3х-1.5у-0.6-1.6у+2.4х=2.7х-3.1у-0.6
    • Автор:

      finn155
    • 5 лет назад
    • 0
  • а) 4(4x-2)+7(1-6x)=16x-8+7-42x=-26x-1б) 0,3(x-5y-2)-0,8(2y-3x)=0,3x-1,5y-0,6-1,6y+2,4x=2,7x-3,1y-0,6
    • Автор:

      lacey100
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years